CONCEPTUAL BASES OF FORMING THE SYSTEM OF FINANCIAL AND ECONOMIC PROVIDING SOCIAL PROTECTION INVOLUNTARILY DISPLACED PERSONS WITH CLUSTER APPROACH - Kropelnytska , S.O.; Solodzhuk , T.V.; Shtefurak , H.V. (The actual problems of regional economy development, 2017)
The article systematizes approaches to financial support and social adaptation of internally displaced persons (IDPs) as well as their social protection, that is based on the analysis of legal framework, situation and sources of financial and social support to the EU member states of the IDPs in Ukraine and their social security. The study of the IDPs situation and the assessment of the required resources are based on a cluster approach, which defines optimal set of problem areas requiring priority social and financial support. This allowed to develop practical recommendations for the development of a comprehensive, transparent and unified policy of social protection through the development of a conceptual framework for the financial and economic provision of social protection IDPs, which will be the basic solution to the problems of social and financial provision forced migrants in Ukraine.